Development and Evaluation of Self Micro Emulsifying Drug Delivery System (SMEDDS) for Nebivolol Hydrochloride: Pharmaceutical Science-SMEDDS for Nebivolol Hydrochloride - Ramya Sri Sura; Subrahmanyam CVS; Shyam Sunder Rachamalla (International Journal of Life Science and Pharma Research, 2022)
The present investigation aimed to prepare a self micro emulsifying drug delivery system (SMEDDS) for the dissolution enhancement of nebivolol hydrochloride. The main objective of this work was to develop, characterize, and evaluate a solid SMEDDS prepared by using the adsorption technique of a liquid SMEDDS to improve the solubility and dissolution rate of nebivolol hydrochloride. The excipients were chosen based on the high solubility of nebivolol hydrochloride, and their concentrations were optimized by constructing ternary phase diagrams. Thirty-two combinations were prepared using oil (Labrafac Lipophile WL 1349), surfactant (Kolliphor RH 40), and co-surfactant (Gelucire 44/14). Self-emulsification time, dilution studies, and thermodynamic stability studies were satisfactory. The in vitro nebivolol release profile showed a faster rate of dissolution compared with the pure nebivolol hydrochloride suspension and marketed formulation. The droplet size was in the range of 132.8±22.1 to 955.7±15.5 nm and zeta potential in the range -7.2±0.53 mV to -46.4±0.32 mV for the selected formulations. Formulation N17 (Labrafac Lipophile WL 1349 -10%w/w, Kolliphor RH40-72%w/w, Gelucire 44/14- 18%w/w) was considered as optimized formulation and showed drug release of 97.26 ± 1.16% in 0.1 N HCl in 120 minutes, the particle size of 132.8±22.1 nm and zeta potential of -46.4±0.32 mV. Thus, the present studies ratify that the bioavailability was improved by nebivolol SMEDDS formulation. The optimized liquid SMEDDS was further used for the preparation of Solid SMEDDS (S-SMEDDS) formulations by using adsorption carriers. The optimized Solid SMEDDS formulation exhibited 95.38 ± 0.76% in vitro drug releases, which was significantly higher than that of the drug solution. The optimized formulation of nebivolol-loaded S-SMEDDS exhibited complete in vitro drug release in 120 min as a compared pure drug solution. The present result confirmed the potential use of SMEDDS to improve the dissolution and oral bioavailability of poorly water-soluble nebivolol.